Assets and Challenges to Recruiting and Engaging Families in a Childhood Obesity Treatment Research Trial: Insights From Academic Partners, Community Partners, and Study Participants - Brock, Donna-Jean P.; Estabrooks, Paul A.; Yuhas, Maryam; Wilson, Jonathon A.; Montague, Danielle; Price, Bryan E.; Elliott, Kenya; Hill, Jennie L.; Zoellner, Jamie M. (Frontiers in Public Health, 2021)
Background: There is need for the childhood obesity treatment literature to identify effective recruitment and engagement strategies for rural communities that are more likely to lack supportive infrastructure for healthy lifestyles and clinical research relative to their urban counterparts. This community case study examines recruitment and engagement strategies from a comparative effectiveness research (CER) trial of two family-based childhood obesity (FBCO) treatment interventions conducted in a medically underserved, rural region. Guided by a Community Based Participatory Research (CBPR) and systems-based approach, the primary aim was to analyze interviews from academic partners, community partners, and study participants for recruitment and engagement assets, challenges, and lessons learned. Methods: Over the three-year lifespan of the study, researchers conducted 300 interviews with Community Advisory Board members (n=14), Parent Advisory Team members (n=7), and study participants (n=100). Using an inductive-deductive approach, interviews were broadly coded for recruitment and engagement assets, challenges, and recommendations; analyzed for descriptive sub-coding; and organized into stakeholder/organization and participant level themes. Codes were analyzed aggregately across time and examined for differences among stakeholders and study participants. Results: Adherence to CBPR principles and development of strong community partnerships facilitated recruitment and engagement; however, variability in recruitment and engagement success impacted partner confidence, threatened outcome validity, and required additional resources. Specifically, assets and challenges emerged around eight key needs. Three were at the stakeholder/organizational level: 1) readiness of stakeholders to conduct CBPR research, 2) development of sustainable referral protocols, and 3) development of participant engagement systems. The remaining five were at the participant level: 1) comfort and trust with research, 2) awareness and understanding of the study, 3) intervention accessibility, 4) intervention acceptability, and 5) target population readiness. Future recommendations included conducting readiness assessments and awareness campaigns, piloting and evaluating recruitment and engagement strategies, identifying participant barriers to engagement and finding a priori solutions, and fostering stakeholder leadership to develop sustainable protocols. Conclusion: Collective findings from multiple perspectives demonstrate the need for multi-leveled approaches focusing on infrastructure supports and strategies to improve stakeholder and participant awareness of, and capacity for, recruiting and engaging medically underserved, rural families in a FBCO CER trial.